2009
DOI: 10.1186/1477-7525-7-42
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure of the Hospital Anxiety and Depression Scale in Japanese psychiatric outpatient and student populations

Abstract: Background: The Hospital Anxiety and Depression Scale (HADS) is a common screening instrument excluding somatic symptoms of depression and anxiety, but previous studies have reported inconsistencies of its factor structure. The construct validity of the Japanese version of the HADS has yet to be reported. To examine the factor structure of the HADS in a Japanese population is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(110 citation statements)
references
References 51 publications
7
101
1
Order By: Relevance
“…We substituted mean values for missing HADS items unless more than six HADS items were missing. The Japanese version's factor structure was consistent with reports from Western countries (Matsudaira et al 2009). …”
Section: Dysphoric Mood In Late Pregnancysupporting
confidence: 84%
“…We substituted mean values for missing HADS items unless more than six HADS items were missing. The Japanese version's factor structure was consistent with reports from Western countries (Matsudaira et al 2009). …”
Section: Dysphoric Mood In Late Pregnancysupporting
confidence: 84%
“…The HADS was translated into Japanese by Kitamura. [31] Although initially the HADS was designed to identify depression and anxiety among a clinical population, Matsudaira et al [32] have confirmed that this measurement also fits nonclinical populations.…”
Section: Questionnairesmentioning
confidence: 90%
“…The HADS has been validated and is widely use to assess anxiety and depression in cancer patients [28]. The construct validity of the Japanese version of the HADS was reported by Matsudaira et al [29]. Seven items each assess anxiety and depression.…”
Section: Endpointsmentioning
confidence: 99%